Separation of Fibrinogen Degradation Products (FDP) by Means of Adsorption to Insolubilized Fibrinmonomer (FM-ag) - Heene, D L; Matthias, F R; Wegrzynowicz, Z; Hocke, G (Thrombosis and Haemostasis, 1979)
The phenomenon of complex formation between fibrinmonomer and fibrinogen degradation products was investigated by means of adsorption of FDP to insolubilized thrombin- modified fibrinogen (FM-ag). Since it could be demonstrated that there are different adsorption characteristics for early FDP and late FDP, the possibility of separation of FDP by means of affinity chromatography on FM-ag columns was evaluated using plasmic digests of 3H-Ac-labelled fibrinogen. The identification of FDP was performed by disc-electrophoresis. The results indicate that the adsorption of early FDP is comparable to the behaviour of fibrinogen, whereas late FDP show essential difference in the affinity towards FM-ag, evident by the result that fragment E adsorbs only to a minimal extent. Fragments D and E derived from fibrinogen as well as from non-crosslinked fibrin, revealed identical adsorption characteristics. Under specified conditions the procedure is suitable as a preparative method for the separation of fragments D and E.